Preparation method of high-strength disposable biological reaction bag
By modifying titanium dioxide and lignin nanoparticles to fill PVA and PE materials, composite membranes are prepared, which solves the problems of the drug's effectiveness and the bag body being easily ruptured by additives in disposable bioreaction bags, and achieves a bioreaction bag with high strength, stability and anti-rupture properties.
Patent Information
- Application Number
- CN202510237213.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-01
- Publication Date
- 2025-04-25
AI Technical Summary
The existing disposable bioreaction bags need to be added to the production process of antioxidants, plasticizers and stabilizers. These additives may cause the effectiveness of the drug to decrease and the bag body is prone to rupture, affecting production stability.
Composite films were prepared by modifying titanium dioxide and modified lignin nanoparticles, filled with PVA and PE materials, and a high-strength disposable bioreaction bag was obtained through coextrusion molding and pressure-keeping cooling processes.
It improves the stability and mechanical properties of the bioreactive bag, reduces the dosage of additives, reduces the risk of decreasing drug effectiveness, and improves the anti-rupture performance of the bag body.
Smart Images

Figure BDA0005293052330000081 
Figure BDA0005293052330000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of disposable bioreactor bag preparation, and in particular to a method for preparing a high-strength disposable bioreactor bag. Background Art
[0002] Disposable systems, also known as single-use systems, have been used in the biopharmaceutical field for more than 30 years and are widely used in multiple processes such as biological reactions, liquid storage, liquid transfer, and sterile filtration. They have the advantages of short construction period, flexible assembly, low cost, high production efficiency, and avoidance of cross contamination. Compared with traditional repeatable systems, disposable systems reduce in-situ cleaning, shorten production turnover, and users will not come into direct contact with the product, reducing the harm of some potentially toxic drugs to the human body.
[0003] Disposable bioreactor bags are an important improvement in biopharmaceutical production, used in processes involving animal cell culture in biopharmaceuticals, as well as new process development and pilot-scale production. The polymer materials used to produce disposable bioreactor bags have the characteristics of strong plasticity, easy transportation, low fixed cost investment, low pollution risk, and high process flexibility. However, it is inevitable to add additives such as antioxidants, plasticizers, and stabilizers during the production process. When these additives come into contact with liquids during the production process of the drug, they may exist in the final drug in the form of leachates, resulting in a decrease in the effectiveness of the drug. In addition, the bag body may rupture during use, which poses new challenges to the production of disposable bioreactor bags. Summary of the invention
[0004] In view of the problems existing in the background technology, the present invention provides a method for preparing a high-strength disposable bioreactor bag, which improves the stability of the bioreactor bag, and is achieved through the following technical solutions:
[0005] The following steps are involved:
[0006] Step (a) Preparation of modified titanium dioxide: drying titanium dioxide in an oven, then weighing a certain amount of titanate coupling agent and adding it to a 90% isopropanol solution for hydrolysis for 2 to 3 hours to obtain a hydrolyzate of the titanate coupling agent, adding the hydrolyzate of the titanate coupling agent to the dried titanium dioxide, heating in a water bath at 70° C., reacting for 3 to 5 hours, filtering and drying to obtain titanium dioxide modified with the titanate coupling agent;
[0007] Step (b) Modified titanium dioxide is filled with PVA material: modified titanium dioxide, PVA powder and dispersant are mixed in proportion;
[0008] Step (c) Preparation of modified lignin: adding lignin nanoparticles to acetic acid solution and mixing evenly, reacting for 10 to 12 hours, leaving the mixture to stand for 24 hours and then placing it in a vacuum drying oven to remove excess water, and then heating it at 140° C. for 2 hours to obtain modified lignin nanoparticles;
[0009] Step (d) Filling PE material with modified lignin nanoparticles: mixing modified lignin nanoparticles and PE powder according to a certain proportion;
[0010] Step (e) preparing a composite film: melt-mixing the modified titanium dioxide-filled PVA material as the outer layer and the modified lignin nanoparticle-filled PE material as the inner layer, respectively, and then feeding the materials through the channels to a die head for co-extrusion molding, and then cooling the materials under pressure on a cold press to obtain a composite film consisting of the inner layer and the outer layer;
[0011] Step (f) processes the composite membrane into a high-strength disposable bioreactor bag.
[0012] Preferably, the titanium dioxide is dried at 110° C. for 2 to 3 hours in step (a).
[0013] Preferably, the titanate coupling agent in step (a) is selected from one or more of titanate coupling agent TMC-101, titanate coupling agent NDZ-201, titanate coupling agent TMC-311, and titanate coupling agent TMC-TTS.
[0014] Preferably, the ratio of the modified titanium dioxide, PVA powder and dispersant in step (b) is selected from one or more of 2:17:1, 3:16:1 and 2.5:16.5:1.
[0015] Preferably, the drying condition in step (c) is drying at 60° C. for 3 to 4 hours.
[0016] Preferably, in step (d), the ratio of the modified lignin nanoparticles to the PE powder is one or more of 1:19, 3:47, 1:24, and 2:18.
[0017] Preferably, the mixing temperature of the melt mixing in step (e) is 190-200° C., and the mixing time is 10-15 minutes.
[0018] Preferably, in step (e), the cold pressing pressure of the cold press is 10 MPa, the cold pressing time is 10 minutes, and the mixture is placed at room temperature for 12 to 15 hours after cold pressing.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The type, form and dispersion of fillers affect the performance of composite materials. When the particle size of the filler is too large, it will cause stress concentration in the matrix, affecting the performance of the material. When the particle size is too small, the dispersion of the filler particles in the matrix will be increased, reducing the mechanical properties of the material. Kaolin is a common filler in plastics. It can make the plastic surface smooth, improve chemical corrosion resistance and insulation performance, but it is easy to cause cracks in the plastic during use. Therefore, the present invention replaces kaolin with titanium dioxide and modifies it to improve the compatibility of the filler with the PVA matrix.
[0021] Mechanical properties are an important characteristic of materials, and the parameters of their mechanical properties affect the application field of materials to a certain extent. The type and amount of filler affect the tensile strength of the composite film. The tensile strength of the composite film obtained by the present invention is 62.3-69.0MPa. After adding modified titanium dioxide and modified lignin, the tensile strength is increased from 40.2MPa and 38.2MPa to 65.6MPa. In addition, after adding modified titanium dioxide and modified lignin, the decomposition temperature of the composite film at 10% weight loss, the decomposition temperature at 20% weight loss, the decomposition temperature at 50% weight loss and the residual amount are also significantly improved. The preparation method of the high-strength disposable bioreactor bag described in the present invention has a simple process, a small amount of additives, and the obtained bioreactor bag has stable performance and is not easy to break. DETAILED DESCRIPTION
[0022] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0023] It should be noted that the experimental methods used in the implementation examples are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0024] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a-b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0025] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0026] In the present invention, unless otherwise specified, all the steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially; for example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially; for example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0027] In the present invention, unless otherwise specified, the specific numerical values and specific substances in the embodiments of the present invention may be combined with other features of the description part of the present invention; for example, if the specification mentions that the reaction temperature is 10-100°C, and the embodiment mentions that the reaction temperature is 20°C, then it can be considered that the present invention has specifically disclosed the range of 10-20°C, or the range of 20-100°C, and this range can be combined with other features of the description part to form a new technical solution.
[0028] Embodiment 1;
[0029] (a) Preparation of modified titanium dioxide
[0030] The titanium dioxide was placed in an oven at 110°C and dried for 2 hours. Subsequently, a certain amount of titanate coupling agent TMC-101 was weighed and added to a 90% isopropanol solution for hydrolysis for 2 hours to obtain a hydrolyzate of the titanate coupling agent TMC-101. 4 kg of the hydrolyzate of the titanate coupling agent TMC-101 was added to 2 kg of the dried titanium dioxide, heated in a water bath at 70°C, reacted for 3 hours, and filtered and dried to obtain titanium dioxide modified with the titanate coupling agent TMC-101.
[0031] (b) Modified titanium dioxide filled PVA material
[0032] Mix modified titanium dioxide, PVA powder and dispersant in a ratio of 2:17:1;
[0033] (c) Preparation of modified lignin
[0034] The lignin nanoparticles were added to the acetic acid solution and mixed evenly, and the mixture was reacted for 10 hours. The mixture was allowed to stand for 24 hours and then dried in a vacuum drying oven at 60° C. for 3 hours to remove excess water, and then heated at 140° C. for 2 hours to obtain modified lignin nanoparticles.
[0035] (d) Modified lignin nanoparticles filled PE materials
[0036] The modified lignin nanoparticles and PE powder were mixed in a ratio of 1:19;
[0037] (e) Preparation of composite membrane
[0038] The modified titanium dioxide-filled PVA material is used as the outer layer, and the modified lignin nanoparticle-filled PE material is used as the inner layer. The mixture is melt-mixed at a temperature of 190°C for 10 minutes, and then flows through each channel to a die head for co-extrusion molding. Subsequently, the mixture is cold-pressed for 10 minutes on a cold press machine with a cold pressing pressure of 10 MPa, and then placed at room temperature for 12 hours for pressure-maintaining cooling to obtain a composite film consisting of an inner layer and an outer layer.
[0039] (f) Processing the composite membrane into a high-strength disposable bioreactor bag.
[0040] Embodiment 2:
[0041] (a) Preparation of modified titanium dioxide
[0042] The titanium dioxide was placed in an oven at 110°C for 2 hours, and then a certain amount of titanate coupling agent TMC-101 was weighed and added to a 90% isopropanol solution for hydrolysis for 2 hours to obtain a hydrolyzate of the titanate coupling agent TMC-101, and 4 kg of the hydrolyzate of the titanate coupling agent TMC-101 was added to 2 kg of the dried titanium dioxide, heated in a water bath at 70°C, reacted for 3 hours, and filtered and dried to obtain titanium dioxide modified with the titanate coupling agent;
[0043] (b) Modified titanium dioxide filled PVA material
[0044] Mix modified titanium dioxide, PVA powder and dispersant in a ratio of 3:16:1;
[0045] (c) Preparation of modified lignin
[0046] The lignin nanoparticles were added to the acetic acid solution and mixed evenly, and the mixture was reacted for 10 hours. The mixture was allowed to stand for 24 hours and then dried in a vacuum drying oven at 60° C. for 3 hours to remove excess water, and then heated at 140° C. for 2 hours to obtain modified lignin nanoparticles.
[0047] (d) Modified lignin nanoparticles filled PE materials
[0048] The modified lignin nanoparticles and PE powder were mixed in a ratio of 1:19;
[0049] (e) Preparation of composite membrane
[0050] The modified titanium dioxide-filled PVA material is used as the outer layer, and the modified lignin nanoparticle-filled PE material is used as the inner layer. The materials are melt-mixed at a temperature of 200°C for 15 minutes, and then flow through each channel to supply the materials to the die head for co-extrusion molding. Subsequently, the materials are cold-pressed for 10 minutes on a cold press machine with a cold pressing pressure of 10 MPa, and then placed at room temperature for 15 hours for pressure-maintaining cooling to obtain a composite film consisting of an inner layer and an outer layer.
[0051] (f) Processing the composite membrane into a high-strength disposable bioreactor bag.
[0052] Embodiment three;
[0053] (a) Preparation of modified titanium dioxide
[0054] The titanium dioxide was placed in an oven at 110°C for 3 hours, and then a certain amount of titanate coupling agent TMC-311 was weighed and added to a 90% isopropanol solution for hydrolysis for 3 hours to obtain a hydrolyzate of the titanate coupling agent TMC-311, and 4 kg of the hydrolyzate of the titanate coupling agent TMC-311 was added to 2 kg of the dried titanium dioxide, heated in a water bath at 70°C, reacted for 4 hours, and filtered and dried to obtain titanium dioxide modified with the titanate coupling agent;
[0055] (b) Modified titanium dioxide filled PVA material
[0056] Mix modified titanium dioxide, PVA powder and dispersant in a ratio of 2.5:16.5:1;
[0057] (c) Preparation of modified lignin
[0058] The lignin nanoparticles were added to the acetic acid solution and mixed evenly, and the mixture was reacted for 11 hours. The mixture was allowed to stand for 24 hours and then dried in a vacuum drying oven at 60° C. for 3 hours to remove excess water, and then heated at 140° C. for 2 hours to obtain modified lignin nanoparticles.
[0059] (d) Modified lignin nanoparticles filled PE materials
[0060] The modified lignin nanoparticles and PE powder were mixed in a ratio of 3:47;
[0061] (e) Preparation of composite membrane
[0062] The modified titanium dioxide-filled PVA material is used as the outer layer, and the modified lignin nanoparticle-filled PE material is used as the inner layer. The materials are melt-mixed at a temperature of 200°C for 13 minutes, and then flow into a die head through each channel for co-extrusion molding. Subsequently, the materials are cold-pressed for 10 minutes on a cold press machine with a cold pressing pressure of 10 MPa, and then placed at room temperature for 13 hours for pressure-maintaining cooling to obtain a composite film consisting of an inner layer and an outer layer.
[0063] (f) Processing the composite membrane into a high-strength disposable bioreactor bag.
[0064] Embodiment 4:
[0065] (a) Preparation of modified titanium dioxide
[0066] The titanium dioxide was placed in an oven at 110°C for 2 hours, and then a certain amount of titanate coupling agent NDZ-201 was weighed and added to a 90% isopropanol solution for hydrolysis for 2 hours to obtain a hydrolyzate of the titanate coupling agent NDZ-201, and 4 kg of the hydrolyzate of the titanate coupling agent NDZ-201 was added to 2 kg of the dried titanium dioxide, heated in a water bath at 70°C, reacted for 5 hours, and filtered and dried to obtain titanium dioxide modified with the titanate coupling agent NDZ-201;
[0067] (b) Modified titanium dioxide filled PVA material
[0068] Mix modified titanium dioxide, PVA powder and dispersant in a ratio of 2.5:16.5:1;
[0069] (c) Preparation of modified lignin
[0070] The lignin nanoparticles were added to the acetic acid solution and mixed evenly, and the mixture was reacted for 11 hours. The mixture was allowed to stand for 24 hours and then dried in a vacuum drying oven at 60° C. for 3 hours to remove excess water, and then heated at 140° C. for 2 hours to obtain modified lignin nanoparticles.
[0071] (d) Modified lignin nanoparticles filled PE materials
[0072] The modified lignin nanoparticles and PE powder were mixed in a ratio of 2:18;
[0073] (e) Preparation of composite membrane
[0074] The modified titanium dioxide-filled PVA material is used as the outer layer, and the modified lignin nanoparticle-filled PE material is used as the inner layer. The materials are melt-mixed at a temperature of 200°C for 15 minutes, and then flow through each channel to supply the materials to the die head for co-extrusion molding. Subsequently, the materials are cold-pressed for 10 minutes on a cold press machine with a cold pressing pressure of 10 MPa, and then placed at room temperature for 15 hours for pressure-maintaining cooling to obtain a composite film consisting of an inner layer and an outer layer.
[0075] (f) Processing the composite membrane into a high-strength disposable bioreactor bag.
[0076] Embodiment five;
[0077] (a) Preparation of modified titanium dioxide
[0078] The titanium dioxide was placed in an oven at 110°C and dried for 3 hours, and then a certain amount of titanate coupling agent TMC-TTS was weighed and added to a 90% isopropanol solution for hydrolysis for 3 hours to obtain a hydrolyzate of the titanate coupling agent TMC-TTS, and 4 kg of the hydrolyzate of the titanate coupling agent TMC-TTS was added to 2 kg of the dried titanium dioxide, heated in a water bath at 70°C, reacted for 5 hours, and filtered and dried to obtain titanium dioxide modified with the titanate coupling agent TMC-TTS;
[0079] (b) Modified titanium dioxide filled PVA material
[0080] Mix modified titanium dioxide, PVA powder and dispersant in a ratio of 3:16:1;
[0081] (c) Preparation of modified lignin
[0082] The lignin nanoparticles were added to the acetic acid solution and mixed evenly, and the mixture was reacted for 12 hours. The mixture was allowed to stand for 24 hours and then dried in a vacuum drying oven at 60° C. for 4 hours to remove excess water, and then heated at 140° C. for 2 hours to obtain modified lignin nanoparticles.
[0083] (d) Modified lignin nanoparticles filled PE materials
[0084] The modified lignin nanoparticles and PE powder were mixed in a ratio of 1:24;
[0085] (e) Preparation of composite membrane
[0086] The modified titanium dioxide-filled PVA material is used as the outer layer, and the modified lignin nanoparticle-filled PE material is used as the inner layer. The materials are melt-mixed at a temperature of 200°C for 15 minutes, and then flow through each channel to supply the materials to the die head for co-extrusion molding. Subsequently, the materials are cold-pressed for 10 minutes on a cold press machine with a cold pressing pressure of 10 MPa, and then placed at room temperature for 15 hours for pressure-maintaining cooling to obtain a composite film consisting of an inner layer and an outer layer.
[0087] (f) Processing the composite membrane into a high-strength disposable bioreactor bag.
[0088] Embodiment six;
[0089] (a) Preparation of modified titanium dioxide
[0090] The titanium dioxide was placed in an oven at 110°C for 2 hours, and then a certain amount of titanate coupling agent NDZ-201 was weighed and added to a 90% isopropanol solution for hydrolysis for 2 hours to obtain a hydrolyzate of the titanate coupling agent NDZ-201, and 4 kg of the hydrolyzate of the titanate coupling agent NDZ-201 was added to 2 kg of the dried titanium dioxide, heated in a water bath at 70°C, reacted for 4 hours, and filtered and dried to obtain titanium dioxide modified with the titanate coupling agent NDZ-201;
[0091] (b) Modified titanium dioxide filled PVA material
[0092] Mix modified titanium dioxide, PVA powder and dispersant in a ratio of 2.5:16.5:1;
[0093] (c) Preparation of modified lignin
[0094] The lignin nanoparticles were added to the acetic acid solution and mixed evenly, and the mixture was reacted for 12 hours. The mixture was allowed to stand for 24 hours and then dried in a vacuum drying oven at 60° C. for 4 hours to remove excess water, and then heated at 140° C. for 2 hours to obtain modified lignin nanoparticles.
[0095] (d) Modified lignin nanoparticles filled PE materials
[0096] The modified lignin nanoparticles and PE powder were mixed in a ratio of 1:24;
[0097] (e) Preparation of composite membrane
[0098] The modified titanium dioxide-filled PVA material is used as the outer layer, and the modified lignin nanoparticle-filled PE material is used as the inner layer. The materials are melt-mixed at a temperature of 200°C for 15 minutes, and then flow through each channel to supply the materials to the die head for co-extrusion molding. Subsequently, the materials are cold-pressed for 10 minutes on a cold press machine with a cold pressing pressure of 10 MPa, and then placed at room temperature for 15 hours for pressure-maintaining cooling to obtain a composite film consisting of an inner layer and an outer layer.
[0099] (f) Processing the composite membrane into a high-strength disposable bioreactor bag.
[0100] Comparative Example 1;
[0101] The difference between this comparative example and Example 1 is that the added titanium dioxide is not modified, and the remaining steps are the same as those of Example 1.
[0102] Comparative Example 2:
[0103] The difference between this comparative example and Example 1 is that the added lignin is not modified, and the remaining steps are the same as those of Example 1.
[0104] Performance Testing
[0105] The composite films obtained in Examples 1 to 6 and Comparative Examples 1 to 2 were made into samples on a universal cutting machine, and the sample size was: 20 mm×5 mm. Performance tests were performed.
[0106] Mechanical properties test
[0107] The tensile test was conducted using an electronic excavation test machine, the implementation standard was GB / T1040-92, and the experimental tensile rate was 20mm / min. The experimental results are shown in the table below.
[0108] Table 1 Tensile test results
[0109]
[0110] Mechanical properties are an important characteristic of materials, and the parameters of mechanical properties affect the application field of materials to a certain extent. As can be seen from the above table, the tensile strengths of Examples 1 to 6 are improved compared with the comparative examples. The tensile strength of Example 1 is improved from 40.2MPa and 38.2MPa to 65.6MPa compared with Comparative Examples 1 and 2, indicating that the modification of titanium dioxide and lignin improves the tensile strength of the composite film.
[0111] Thermogravimetric analysis
[0112] Thermogravimetric analyzer was used to characterize the thermal decomposition properties of the composite materials. The test conditions were a nitrogen atmosphere, a test temperature of 20°C to 500°C, and a heating rate of 15°C / min.
[0113] Table 2 Thermogravimetric analysis test results
[0114]
[0115]
[0116] The decomposition temperatures of Examples 1 to 6, the decomposition temperatures of 10% weight loss, 20% weight loss, 50% weight loss and the residual amount of the composite films after adding modified titanium dioxide and modified lignin are significantly improved compared with the control example.
[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a high-strength disposable bioreactor bag, characterized in that: The following steps are involved: Step (a) Preparation of modified titanium dioxide: drying titanium dioxide in an oven, then weighing a certain amount of titanate coupling agent and adding it to a 90% isopropanol solution for hydrolysis for 2 to 3 hours to obtain a hydrolyzate of the titanate coupling agent, adding the hydrolyzate of the titanate coupling agent to the dried titanium dioxide, heating in a water bath at 70° C., reacting for 3 to 5 hours, filtering and drying to obtain titanium dioxide modified with the titanate coupling agent; Step (b) Modified titanium dioxide is filled with PVA material: modified titanium dioxide, PVA powder and dispersant are mixed in proportion; Step (c) Preparation of modified lignin: adding lignin nanoparticles to acetic acid solution and mixing evenly, reacting for 10 to 12 hours, leaving the mixture to stand for 24 hours and then placing it in a vacuum drying oven to remove excess water, and then heating it at 140° C. for 2 hours to obtain modified lignin nanoparticles; Step (d) Filling the modified lignin nanoparticles with PE material: mixing the modified lignin nanoparticles and PE powder in proportion; Step (e) preparing a composite film: melt-mixing the modified titanium dioxide-filled PVA material as the outer layer and the modified lignin nanoparticle-filled PE material as the inner layer, respectively, and then feeding the materials through the channels to a die head for co-extrusion molding, and then cooling the materials under pressure on a cold press to obtain a composite film consisting of the inner layer and the outer layer; Step (f) processes the composite membrane into a high-strength disposable bioreactor bag.
2. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: The drying condition of the titanium dioxide in step (a) is 110° C. for 2 to 3 hours.
3. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In the step (a), the titanate coupling agent is selected from one or more of titanate coupling agent TMC-101, titanate coupling agent NDZ-201, titanate coupling agent TMC-311, and titanate coupling agent TMC-TTS.
4. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: The ratio of the modified titanium dioxide, PVA powder and dispersant in the step (b) is selected from one or more of 2:17:1, 3:16:1 and 2.5:16.5:
1.
5. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: The drying condition in the step (c) is drying at 60° C. for 3 to 4 hours.
6. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In the step (d), the ratio of the modified lignin nanoparticles to the PE powder is one or more of 1:19, 3:47, 1:24, and 2:
18.
7. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: The mixing temperature of the melt mixing in step (e) is 190-200° C., and the mixing time is 10-15 minutes.
8. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In the step (e), the cold pressing pressure of the cold press is 10 MPa, the cold pressing time is 10 minutes, and the mixture is placed at room temperature for 12 to 15 hours after the cold pressing.